2020
DOI: 10.1007/s11469-020-00296-y
|View full text |Cite
|
Sign up to set email alerts
|

General and Alcohol-Related Social Media Use and Mental Health: a Large-Sample Longitudinal Study

Abstract: The current study aimed to investigate if general and alcohol-related social media use predicts symptoms of depression and anxiety. Students in Bergen, Norway, participated in a Web-based survey during fall 2015 (T1) and a follow-up survey during fall 2016 (T2). A total of 5217 participated in both surveys. Crude and adjusted linear regression analyses were conducted to investigate if social media use at T1 predicted depression and anxiety at T2. Several social media use variables (e.g., using Instagram) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
6
2
Order By: Relevance
“…Higher utilization of social media was related to higher alcohol and/or substance use. These findings are consistent with previous research that has examined a definitive diagnosis of a substance use disorder with use of social media (Erevik et al 2020;Lyers et al 2020). Moreno et al (2016) noted that social media conveys messages about the acceptability regarding the types and amount of alcohol and/or substance use that may be acceptable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher utilization of social media was related to higher alcohol and/or substance use. These findings are consistent with previous research that has examined a definitive diagnosis of a substance use disorder with use of social media (Erevik et al 2020;Lyers et al 2020). Moreno et al (2016) noted that social media conveys messages about the acceptability regarding the types and amount of alcohol and/or substance use that may be acceptable.…”
Section: Discussionsupporting
confidence: 89%
“…While these studies did not explore users' means of coping with the increased symptoms of anxiety and insomnia, the findings do suggest that additional exploration about the impact of social media use during crises is warranted (SAMHSA 2020), as well as the fact that individuals with insomnia are known to be at increased risk for substance misuse (NIDA 2020). In addition, while other research has documented the relationship between alcohol and/or substance use and use of social media (Erevik et al 2020;Lyers et al 2020), little is known about the relationship between social media and negative coping-for example, via alcohol or other substance use-during a global pandemic, particularly within the general population (Wiederhold 2020).…”
mentioning
confidence: 99%
“…Despite these concerns, several authors have reported the positive role of social media in new product development, SMEs business sustainability, public dissemination and discussion of vital information about the COVID-19 pandemic ( Rakshit et al, 2021 ; Talwar at al., 2022 ; Yousaf et al, 2022 ; Das and Ahmed, 2020 ), as well as in offering an online support network for those in need; for instance, people used social media to support each other during the pandemic ( Khaleej Times, 2021 ). In contrast to Longobardi et al’s (2020) findings, Erevik et al (2020) found an inverse relationship between the number of online friends and symptoms of depression, suggesting that having more social media followers may protect against the development of depressive symptoms. Similarly, Cole et al (2017) reported the benefits of using social media as a social support medium.…”
Section: Development Of a Mental Health Index And Study Hypothesescontrasting
confidence: 92%
“…De Choudhury et al (2013) used social media content to detect and diagnose major depressive disorders. Erevik et al (2020) used the number of social media connections and frequency of logins to understand the impact of follower count on user depression.…”
Section: Development Of a Mental Health Index And Study Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation